A New Technique To Enhance Levator Power in Congenital Ptosis - Dr. Mrinmay Nandi (Indian Journal of Plastic Surgery)
Severe degree of congenital Ptosis, not correctable by resection of levator alone poses a formidable challenge. Results with classical technique of brow suspension with frontalis sling, leaves much to be desired. Improved version of this technique is tried on seven patients and appears to be superior.